2012
DOI: 10.1111/php.12006
|View full text |Cite
|
Sign up to set email alerts
|

Increased Antioxidant Activity and Changes in Phenolic Profile of Kalanchoe pinnata (Lamarck) Persoon (Crassulaceae) Specimens Grown Under Supplemental Blue Light

Abstract: Antioxidant compounds protect plants against oxidative stress caused by environmental conditions. Different light qualities, such as UV-A radiation and blue light, have shown positive effects on the production of phenols in plants. Kalanchoe pinnata (Lamarck) Persoon (Crassulaceae) is used for treating wounds and inflammations. Some of these beneficial effects are attributed to the antioxidant activity of plant components. We investigated the effects of blue light and UV-A radiation supplementation on the tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 61 publications
1
36
1
3
Order By: Relevance
“…Many flavonoids have been previously described in this species, including the compounds isolated in this study (Muzitano et al, 2006a(Muzitano et al, , 2006bTatsimo et al, 2012). The literature reports that compound 1 (diglycosylated flavonoid) showed antiallergic actions (Ichikawa, Ogura, Lijima, 1986), high antioxidant potential (Nascimento et al, 2013) and antileishmanial activities (Muzitano et al, 2006a). Moreover, quercetrin (2) protected skin from UVB-induced inflammation (Yin et al, 2013), displayed antioxidant (Aderogba, Okoh, Idowu, 2005;Tai et al, 2014) and antileishmanial activities (Muzitano et al, 2006b), showed antiproliferative and apoptotic effects in colon cancer cells (Cincin et al, 2015), demonstrated gastroprotective actions (Mota et al, 2009) and showed intestinal anti-inflammatory effects (Camuesco et al, 2004).…”
Section: Resultsmentioning
confidence: 69%
“…Many flavonoids have been previously described in this species, including the compounds isolated in this study (Muzitano et al, 2006a(Muzitano et al, , 2006bTatsimo et al, 2012). The literature reports that compound 1 (diglycosylated flavonoid) showed antiallergic actions (Ichikawa, Ogura, Lijima, 1986), high antioxidant potential (Nascimento et al, 2013) and antileishmanial activities (Muzitano et al, 2006a). Moreover, quercetrin (2) protected skin from UVB-induced inflammation (Yin et al, 2013), displayed antioxidant (Aderogba, Okoh, Idowu, 2005;Tai et al, 2014) and antileishmanial activities (Muzitano et al, 2006b), showed antiproliferative and apoptotic effects in colon cancer cells (Cincin et al, 2015), demonstrated gastroprotective actions (Mota et al, 2009) and showed intestinal anti-inflammatory effects (Camuesco et al, 2004).…”
Section: Resultsmentioning
confidence: 69%
“…Particularly active were α-rhamnoisorobin (23) (IC 50 = 0.71 µg/mL) [28] and quercetin 3-O-α-L-arabinopyranosyl-(1 → 2)-α-L-rhamnopyranoside (29) (EC 50 = 1.41 µg/mL) [90].…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Hence, blue (B) and red (R) LED light absorbed by photosynthetic pigments are more effective than other wide-spectrum light [6]. B light is associated with physiological responses such as plant photo-morphogenesis, phototropism, vegetative growth, stomatal opening, leaf expansion, anatomy and photosynthetic functioning, enzyme synthesis, chloroplast movement, and gene expression [6][7][8][9][10][11]. The range of wavelengths of B light impacting growth of plants is diverse and crop-specific [10,12].…”
Section: Introductionmentioning
confidence: 99%